Educational Metaphors in Mencius: Conceptual Mappings and Translation Strategies - Wu, Lin; Ma, Xinyu (Journal of Educational Research and Policies, 2026)
This study examines five educational metaphors in Mencius through Conceptual Metaphor Theory: three teacher metaphors (THE TEACHER IS A CRAFTSMAN, THE TEACHER IS A NURTURER, THE TEACHER IS A FAMILY ELDER) and two teaching metaphors (TEACHING IS NATURAL NOURISHMENT, TEACHING IS DRAWING THE BOW WITHOUT RELEASING). The teacher metaphors construe the teacher as a craftsman bound by technical limits, as a cultivator fostering natural growth, and as a moral exemplar bearing familial responsibility. The teaching metaphors structure instruction as context-sensitive nourishment and as deliberate restraint that elicits learner agency. Comparative analysis of James Legge's and D.C. Lau's translations of these metaphors reveals a systematic tension between preserving culturally specific imagery and securing target-language accessibility. Legge preserves source-domain materiality and places the interpretive burden on the reader. Lau recodes metaphors into abstract, psychologized terms and shoulders that burden to ensure immediate fluency. This divergence is not merely a linguistic choice but an intercultural negotiation between Chinese and Anglo-American epistemic frameworks that shapes how readers conceptualize the nature of education.